A new species of Amblydromalus Chant & McMurtry (Acari: Mesostigmata: Phytoseiidae) from Brazil, with a key to Brazilian species of the genus - Demite, Peterson R.; Cavalcante, Ana Cristina C.; Lofego, Antonio C. [UNESP] (Systematic and Applied Acarology Society, 2019)
A new species, Amblydromalus itacoatiarensissp. nov. is described and illustrated based on adults of both sexes. It was found in association with plants in natural and agro-ecosystems, in Amazonas state, Brazil. A key to Brazilian species of the genus is provided.
Keywords: Amazon Biome; Amblyseiinae; biological control; Euseiini; predatory mites